The Importance of Communication Strategies in Implementing the Dissemination of Development Innovations: A Case Study of the Communications and Information Office of North Sumatra - Alfikri, Muhammad (Technium Social Sciences Journal, 2021)
One way to regulate the implementation of a communication process, from planning, implementation to evaluation to achieve a goal. The problem in this research is how to implement the communication strategy of the North Sumatra Communication and Information Office in disseminating development innovations. This type of research is qualitative research. Informants in this study were the heads of the Department of Communication and Information, employees, public relations department, community leaders, journalists, and the general public. The technique of determining the informants using purposive sampling. To obtain data from informants used in-depth interview research techniques, observation, and documentation. While the data analysis mechanism is carried out by data reduction and data presentation. The results of this study found that the communication strategy carried out by the Communication and Information Office of North Sumatra was to build a network that guides the actions taken and at the same time, meaning that after working together Understanding the nature and meaning of a development innovation goal, then determining strategies to achieve these development goals. The form of communication strategy that has been implemented by the Communication and Information Office of North Sumatra is in the form of a communication development program through dialogue with mass media, such as KIM, workshops, interactive dialogue, outdoor media, and calendar printing